EFFECT OF VITAMIN E AND SELENIUM ON BODY WEIGHT OF MERIZ DOES AND IT'S KIDS AND MILK PRODUCTION AND CONSTITUENTS - Saeb Y Abdul–Rahman; Wassem Khalid Ahmed Khrofa (Mesopotamia Journal of Agriculture, 2018)
The study was conducted on 21 pregnant Meriz Does investigate the effect of injection Vit E and Sodium Selenite during pregnancy and suckling stage on their kids , Milk yield and it's constituents. The animals were divided into three treatments (7 heads / treatment) ,control treatment was injected weekly subcutaneous with 1ml of normal saline, the second treatment was injected weekly with(2mg ofVit E and 40 µg Sodium Selenite) /Kg of body weight , the third treatment was injected weekly with (4mg of Vit E and 80 µg Sodium Selenite) / Kg of body weight. The results revealed that treating with Vit E and Sodium Selenite led to a significant increase (P ≤ 0.05) in does bodyweights during the1st , 2ndand3rd month of suckling in the (2nd and 3rd) treatment compared with control, and a significant increase (P ≤ 0.05) in the Kid's weight at birth in the in 2nd and 3rd groups compared with control group during (2nd and 3rd) month of lactation , as well as , a significant increase of Kids body weight in the 3rd group during 1st month of lactation compared with other treatments. and in regard to the milk production and constituents , treatments with vitamin E and Sodium Selenite in 3rd group causes a significant increase in daily milk yield along Lactation period as compared with control group , also a significant increase in milk fat quantity on the 2nd and 12th week in 3rd group and a significant increase in milk protein quantity in 3rd group along the lactation except the 4th week m and a significant decrease in milk lactose quantity on 6th , 8th , 10th and 12th week of lactation.